Abiotic factors and photosynthetically active photon density affect the physiological mechanisms of jaboticaba - Ester dos S. Coêlho; João E. da S. Ribeiro; Elania F. da Silva; Toshik I. da Silva; Pablo H. de A. Oliveira; Thiago J. Dias; Aurélio P. Barros Júnior; Daniel V. Silva; Ronald M. Rodriguez (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT In fruit species, the amount of solar energy absorbed can influence fruit quality; hence, ensuring optimal light distribution management in the canopy of plants is essential. Therefore, the objectives of this study were (i) to analyze the variations in gas exchange through the day and (ii) identify the photosynthetically active photon flux density (PPFD) that promotes higher chlorophyll fluorescence and electron transport rate in jaboticaba seedlings. The experimental design was completely randomized, with treatments consisting of 18 photosynthetic photon flux densities and three evaluations throughout the day. Six replicates were used, with two plants per plot. Gas exchange and chlorophyll a fluorescence in P. peruviana were altered due to fluctuating photosynthetic photon flux density (0; 25; 50; 75; 100; 125; 150; 175; 200; 400; 600; 800; 1,000; 1,200; 1,400; 1,600; 1,800; and 2,000 μmol m-2 s-1) and environmental conditions throughout the day (8:00 a.m., 12:00 and 4:00 p.m.). The higher PPFD (1,384.6 μmol m-2 s-1) and air temperature (39.74 °C) at noon (12:00 p.m.) favored gas exchange in this species. An increase in PPFD of up to 1,000 μmol m-2 s-1 positively influenced the gas exchange and chlorophyll a fluorescence of P. peruviana.